2022
DOI: 10.1093/jimb/kuac010
|View full text |Cite
|
Sign up to set email alerts
|

Survey of nonconventional yeasts for lipid and hydrocarbon biotechnology

Abstract: Non-conventional yeasts have an untapped potential to expand biotechnology and enable process development necessary for a circular economy. They are especially convenient for the field of lipid and hydrocarbon biotechnology because they offer faster growth than plants, easier scalability than microalgae and exhibit increased tolerance relative to some bacteria. The ability of industrial organisms to import and metabolically transform lipids and hydrocarbons are crucial in such applications. Here, we assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Remarkably, the growth of C. maltosa on TOD SF2 wax was statistically indistinguishable from growth on glucose, with a pairwise p-value of 0.06. Previous work showed that C. maltosa could achieve comparable growth to glucose with 1tetradecanol as the sole carbon source, 47 and this work now shows it can do the same with a complex mixture of hydrocarbons and other organic molecules.…”
Section: ■ Results and Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Remarkably, the growth of C. maltosa on TOD SF2 wax was statistically indistinguishable from growth on glucose, with a pairwise p-value of 0.06. Previous work showed that C. maltosa could achieve comparable growth to glucose with 1tetradecanol as the sole carbon source, 47 and this work now shows it can do the same with a complex mixture of hydrocarbons and other organic molecules.…”
Section: ■ Results and Discussionsupporting
confidence: 58%
“…These two species were used in this study because prior work characterized their substrate range and showed their ability to utilize hydrocarbons, fatty acids, and fatty alcohols, similar to the ones in the TOD composition, as their sole carbon source. 47 C. maltosa showed superior growth on TOD SF2 wax (final OD 600 of 2.0) compared to the other HDPE-derived substrates (final OD 600 of 0.64 for TOD SF1 wax, 0.32 for TOD liquid, 0.22 for pyrolysis SF1 wax, and 0.24 for pyrolysis SF2 wax; all with p-value <0.05 when compared to TOD SF2) as shown in Figure 3. Remarkably, the growth of C. maltosa on TOD SF2 wax was statistically indistinguishable from growth on glucose, with a pairwise p-value of 0.06.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
See 3 more Smart Citations